2010
DOI: 10.1097/id.0b013e3181cec8bc
|View full text |Cite
|
Sign up to set email alerts
|

CTX Biochemical Marker of Bone Metabolism. Is It a Reliable Predictor of Bisphosphonate-Associated Osteonecrosis of the Jaws After Surgery? Part II: A Prospective Clinical Study

Abstract: Biochemical markers of bone metabolism have been used in medicine to evaluate and provide treatment to patients with metabolic bone diseases, such as osteoporosis. Serum cross-linked C-telopeptide of type I collagen (CTX) is a marker of osteoclast activity and is used to assess the level of bone resorption. Recently, in oral and maxillofacial surgery, it was proposed that the levels of serum CTX may predict the subsequent risk of developing osteonecrosis of the jaws (ONJ) after oral surgery procedures for pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 22 publications
0
35
1
3
Order By: Relevance
“…Thus, this analysis reported no association between low serum CTX levels (100 pg/mL) and ONJ in osteoporosis 27,28 . A recent small, prospective study investigated the potential role of serum CTX monitoring to assess the risk for ONJ in osteoporosis patients on oral BPs undergoing oral surgery 29 . A control group that consisted of n = 109 patients taking oral BPs did not take the CTX test preoperatively.…”
Section: Biochemical Markers Of Bone Turnover In Onjmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, this analysis reported no association between low serum CTX levels (100 pg/mL) and ONJ in osteoporosis 27,28 . A recent small, prospective study investigated the potential role of serum CTX monitoring to assess the risk for ONJ in osteoporosis patients on oral BPs undergoing oral surgery 29 . A control group that consisted of n = 109 patients taking oral BPs did not take the CTX test preoperatively.…”
Section: Biochemical Markers Of Bone Turnover In Onjmentioning
confidence: 89%
“…Recently, data from four studies of zoledronic acid, including the Health Outcomes and Reduced Incidence with Zoledronic Acid Once Yearly (HORIZON) Pivotal Fracture Trial in postmenopausal women, a recurrent fracture prevention study in patients with previous hip fracture, a glucocorticoid‐induced osteoporosis study, and a male osteoporosis study, were pooled, and serum CTX data from n = 11,000 patients were examined 27,28 . Only two cases of adjudicated ONJ (one in a placebo patient and one in a zoledronic acid‐treated patient) were reported and have been previously described 27–29 . The serum CTX levels of the placebo patient diagnosed with ONJ were >260 pg/mL.…”
Section: Biochemical Markers Of Bone Turnover In Onjmentioning
confidence: 99%
“…İlaca ara verilmesinin İÇKON insidansını değiştirdiği konusunda bilimsel bir kanıt bulunmamaktadır. ADA bilimsel kurulu 2011 yılında BPs'lerin düşük birikim dozunda (2 yıldan az kullanım) ve denosumab kullanan hastalarda ilaca ara verilmesine gerek olmadığını bildirmektedir 74 . Bununla birlikte ilaca ara verilmesinin, yüksek birikim dozuna maruz kalan hastalarda (4 yıldan uzun süreli kullanım) ve romatoid artrit, önceden veya halen devam eden kortikosteroid tedavisi, diabetus mellitus ve yara iyileşmesi tamamlanana kadar olan sürede sigara kullanımı gibi eşlik eden durumlarda yararlı olduğu da bildirilmektedir.…”
Section: Tedavi̇unclassified
“…An expert panel recommended that using this test may not be an evidence-based approach as a control group was missing in the initial study [99]. Other authors also commented on the lack of quality evidence with regard to the predictive value of CTX [100] while a study with limited followup concluded that serum CTX is not a valid preoperative test to accurately assess the level of risk of developing ONJ and is not indicated in the oral surgery patient [101]. Because ONJ can be a devastating complication of bisphosphonate therapy, a collaborative effort between dentists and physicians in deciding on the patient's dental treatment is recommended, because it can minimize complications and adverse events.…”
Section: Osteonecrosis Of the Jaws (Onj)mentioning
confidence: 99%